Gaming disorder and problematic caffeine consumption in adolescents: a narrative review and public health framework - Park, Jennifer J.; Zhao, Yihong; Potenza, Marc N. (Frontiers in Psychology, 2025)
Caffeinated beverages, particularly energy drinks, appear to be frequently consumed by adolescents during gaming sessions. This may be in part due to the normalization of caffeine use within gaming culture, where energy drinks are marketed as performance-enhancing tools and symbols of the “gamer” identity. Given evidence of the relationships between gaming disorder (GD) and problematic caffeine consumption (PCC), a narrative review was conducted to synthesize the current literature on GD/gaming and PCC/caffeine use in adolescents. Eight key topics emerged from the literature: (1) the associations between GD/gaming and PCC/caffeine use; (2) the need for increased regulation of caffeine sales and marketing in gaming contexts; (3) parental and peer influences on caffeine use; (4) health and marketing literacy related to caffeinated products; (5) sex-specific patterns in gaming-related caffeine consumption; (6) overlapping neurocognitive mechanisms underlying GD and PCC; (7) self- or peer-enacted strategies for reducing caffeine intake; and (8) shared negative consequences of GD and PCC. These findings reveal multiple interacting influences that may reinforce both behaviors and have been used to propose a public health framework to inform future research, intervention, and policy to promote and protect the health of adolescents who consume caffeine and game.